Dante e l'arte - Universitat Autònoma de Barcelona. Institut d'Estudis Medievals (Universitat Autònoma de Barcelona, 2014)
Dante e l'Arte aims at studying and highlighting the central role of Dante in the artistic creation of his time and its aftermath up to the present. The standard structure of the journal consists of two parts: in the first one, exclusive attention is paid to every artistic mode (iconography, drama, music, etc.) within Dante's work; the second part is devoted to the reception of Dante's work in the different artistic modes (drama, visual arts and theater, music, literature, etc.) up till now.
Keywords: Dante Alighieri, : 1265-1321 : Art : Periodicals; Dante Alighieri, : 1265-1321 : Influence : Art : Periodicals; Dante Alighieri, : 1265-1321; Art